Rational expectations in a macromodel: Some comparative analyses with Finnish data - Ari Lahti; Matti Virén (Bank of Finland, 1988)
This paper reports some policy experiments carried out with the QMED model of the Bank of Finland. The main issue in these experiments is the role of expectations. Thus, we compare a static expectations version with two rational expectations versions of the model. These two versions differ in terms of the time horizon of expectations. When various policy simulations are carried out with these different versions - both in terms of anticipated and unanticipated shocks - it turns out that the whole short-run dynamics ;s crucially affected by the way in which expectations are modelled. In particular, we find the advance effects in the case of the rational expectat;ons versions can be of considerable magnitude.
URN:NBN:fi:bof-201807301736
Keywords: 330